SUBSTITUTION OF STARTER PIG FEED WITH CORN AND SOIL WORM FLOUR ON IT’S PERFORMANCE AND ECONOMIC VALUE - Pratama, I Made Kerta; Ardana, Ida Bagus Komang; Budiasa, I Ketut (Buletin Veteriner Udayana; Vol. 14 No. 6 December 2022DO - 10.24843/bulvet.2022.v14.i06.p02, 2022)
This study aims to determine the effect of substitution of starter pork feed with corn flour and earthworm flour on performance and economic value. This study used 24 tails of weaning piglets which were fed corn flour and earthworm meal ( Lumbricus rubellus ) in their feed for 30 days. Each treatment group consisted of 6 animals’ piglets are (P 0 ) as control given cornstarch and flour 9% earthworm 1%, (P 2 ) given 8.5% corn flour and flour earthworm 1.5%, (P3) given 8% corn flour 2% earthworm flour in the feed. The results of substitution of corn flour and earthworm flour had a significant effect (P<0.05) on body weight gain, total feed consumption, feed conversion and economic value. It can be concluded that the substitution of corn flour and earthworm flour can improve the performance of weaning piglets.